2015
DOI: 10.1534/genetics.115.176834
|View full text |Cite
|
Sign up to set email alerts
|

The Rate and Molecular Spectrum of Spontaneous Mutations in the GC-Rich Multichromosome Genome of Burkholderia cenocepacia

Abstract: Spontaneous mutations are ultimately essential for evolutionary change and are also the root cause of many diseases. However, until recently, both biological and technical barriers have prevented detailed analyses of mutation profiles, constraining our understanding of the mutation process to a few model organisms and leaving major gaps in our understanding of the role of genome content and structure on mutation. Here, we present a genome-wide view of the molecular mutation spectrum in Burkholderia cenocepacia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
84
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(106 citation statements)
references
References 74 publications
16
84
4
2
Order By: Relevance
“…Using this data set, we estimate a bpsm rate of 0.001 (6.02 3 10 25 )/genome/generation, an indel rate of 0.0002 (2.62 3 10 25 ) /genome/generation, and a rate of plasmid loss of 1.67 3 10 25 (8.17 3 10 26 )/genome/generation (SEM). which are similar to the rates that we reported previously but reflect the differences in our data sets described above (Dillon et al 2015).Among the 43 MA lineages, 233 bpsms, 42 short indels, and four plasmid loss events were identified. The most common class of bpsms was missense bpsms (141), followed by synonymous bpsms (49), intergenic bpsms (37), and nonsense bpsms (6).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Using this data set, we estimate a bpsm rate of 0.001 (6.02 3 10 25 )/genome/generation, an indel rate of 0.0002 (2.62 3 10 25 ) /genome/generation, and a rate of plasmid loss of 1.67 3 10 25 (8.17 3 10 26 )/genome/generation (SEM). which are similar to the rates that we reported previously but reflect the differences in our data sets described above (Dillon et al 2015).Among the 43 MA lineages, 233 bpsms, 42 short indels, and four plasmid loss events were identified. The most common class of bpsms was missense bpsms (141), followed by synonymous bpsms (49), intergenic bpsms (37), and nonsense bpsms (6).…”
supporting
confidence: 90%
“…MA studies have been used to characterize the fitness effects of spontaneous mutations in Drosophila melanogaster (Bateman 1959;Mukai 1964;Keightley 1994;Fry et al 1999) A more powerful approach for studying the fitness effects of spontaneous mutations is to pair MA experiments with wholegenome sequencing (MA-WGS), so that both the genetic basis and fitness effects of a collection of mutations can be known. MA-WGS studies have been conducted in a diverse array of bacteria, generating a growing database of naturally accumulated mutations that has dramatically improved estimates of mutation rates and spectra (Lee et al 2012;Sung et al 2012Sung et al , 2015Heilbron et al 2014;Long et al 2014Long et al , 2015Dillon et al 2015;Foster et al 2015;Dettman et al 2016). Yet, only one of these studies has also characterized the fitness of MA-WGS lines (Heilbron et al 2014), and this study was conducted with mutator lineages, which have altered base substitution and indel biases and produce hundreds of mutations per line (Lee et al 2012;Sung et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of deviation from average GC% suggests instead that substitutions are not biased toward A+T in Burkholderia leaf nodule symbionts. This interpretation is supported by experimental data demonstrating an unusual mutational bias toward G+C in other Burkholderia species (Dillon et al, 2015).…”
Section: Horizontal Gene Transfer Between Obligate Leaf Nodule Symbiosupporting
confidence: 62%
“…Longterm mutation accumulation studies showed that B. cenocepacia has low genome-wide mutation rates, with many of the mutations biased toward deletions (Dillon et al 2015). Longitudinal sampling spanning up to 10 yr allowed us to ask if genome reduction occurs during the adaption of B. cenocepacia in CF patients.…”
Section: Recurrent Genomic Changes In B Cenocepacia During Long-termmentioning
confidence: 99%